Analysis Of Vortex-Induced Vibration Characteristics For A Three-Dimensional Flexible Tube - Zhipeng Feng; Huanhuan Qi; Pingchuan Shen; Fenggang Zang; Yixiong Zhang (Zenodo, 2016)
Numerical simulations of vortex-induced vibration of a three-dimensional flexible tube under uniform turbulent flow are calculated when Reynolds number is 1.35×10 4 . In order to achieve the vortex-induced vibration, the three-dimensional unsteady, viscous, incompressible Navier-Stokes equation and LES turbulence model are solved with the finite volume approach, the tube is discretized according to the finite element theory, and its dynamic equilibrium equations are solved by the Newmark method. The fluid-tube interaction is realized by utilizing the diffusion-based smooth dynamic mesh method. Considering the vortex-induced vibration system, the variety trends of lift coefficient, drag coefficient, displacement, vertex shedding frequency, phase difference angle of tube are analyzed under different frequency ratios. The nonlinear phenomena of locked-in, phase-switch are captured successfully. Meanwhile, the limit cycle and bifurcation of lift coefficient and displacement are analyzed by using trajectory, phase portrait, and Poincaré sections. The results reveal that: when drag coefficient reaches its minimum value, the transverse amplitude reaches its maximum, and the “lock-in” begins simultaneously. In the range of lock-in, amplitude decreases gradually with increasing of frequency ratio. When lift coefficient reaches its minimum value, the phase difference undergoes a suddenly change from the “out-of-phase” to the “in-phase” mode. : {"references": ["Goverdhan R, Williamson C H K. Vortex induced vibrations (J). Annual Review Fluid Mechanics, 2004, 36: 413-455.", "Feng C C. The measurement of vortex-induced effect in the flow past stationary and oscillating circular cylinder and D-section cylinders (D). Vancouver: University of British Columbia, 1968.", "Griffin O M. Vortex-excited cross flow vibrations of a single circular cylinder (J). ASME Journal of Pressure Vessel Technology, 1980, 102: 258-166.", "Griffin O M, Ramberg S E. Some recent studies of vortex-excited shedding with application to marine tubulars and risers (J). ASME: Journal of Energy Resources Technology, 1982, 104: 2-13.", "Khalak A, Williamson C H K. Motions, forces and mode transitions in vortex-induced vibrations at low mass-damping (J). Journal of Fluids and Structures, 1999, 13(7-8): 813-851.", "Govardhan R, Williamson C H K. Modes of vortex formation and frequency response for a freely vibrating cylinder (J). Journal of Fluid Mechanics, 2000, 420: 85-130.", "Evangelinos C. Parallel dimulations of vortex-induced vibrations in turbulent flow: linear and non-linear models (D). Providence: Brown University, 1999.", "Evangelinos C, Lucor D, Karniadakis G E. DNS-derived force distribution on flexible cylinders subject to vortex-induced vibration (J). Journal of Fluids and Structures, 2000, 14(3): 429-440.", "Nomura T. Finite element analysis of vortex-induced vibrations of bluff cylinders (J). Journal of Wind Engineering and Industrial Aerodynamics, 1993, 46-47: 587-594.\n[10]\tMittal S, Kumar V. Finite element study of vortex-induced cross-flow and in-line oscillations of a circular cylinder (J). International Journal for Numerical Methods in Fluids, 1999, 31: 1087-1120.\n[11]\tZhou C Y, So R M, Lam K. Vortex-induced vibrations of an elastic circular cylinder (J). Journal of Fluids and Structures, 1999, 13(2): 165-189.\n[12]\tMeneghini J R, Bearman P W. Numerical simulation of high amplitude oscillatory flow about a circular cylinder (J). Journal of Fluids and Structures, 1995, 9 (4): 435-455.\n[13]\tJadic I, So R M C, Mignolet P. Analysis of fluid-structure interactions using a time-marching technique (J). Journal of Fluids and Structures, 1998, 12(6): 631-654.\n[14]\tPlaczek A, Sigrist J F. Numerical simulation of an oscillating cylinder in a cross-flow at low Reynolds number: Forced and free oscillations (J). Computers & Fluids, 2009, 38:80-100.\n[15]\tMittal S, Kumar V. Flow-induced vibration of a light circular cylinder at Reynolds numbers 103 to 104 (J). Journal of Sound and Vibration, 2001, 245(5): 923-946.\n[16]\tLi T, Zhang J Y, Zhang W H. Nonlinear characteristics of vortex-induced vibration at low Reynolds number (J). Commun Nonlinear Sci Numer Simulat, 2011, 16: 2753-2771.\n[17]\tGabbai R D, Benaroya H. An overview of modeling and experiments of vortex-induced vibration of circular cylinders (J). Journal of Sound and Vibration, 2005, 282: 575-616.\n[18]\tSarpkaya T. A critical review of the intrinsic nature of vortex-induced vibrations(J). Journal of Fluids and Structures, 2004, 19: 389-447. \n[19]\tBenhamadouche S, Laurence D. LES, coarse LES, and transient RANS comparisons on the flow across a tube bundle (J). International Journal of Heat and Fluid Flow, 2003, 24: 470-479.\n[20]\tWANG X C. The finite element method (M). Beijing: Tsinghua University Press, 2003: 468-495.\n[21]\tNorberg C. Fluctuating lift on a circular cylinder: review and new measurements (J). Journal of Fluids and Structures, 2003, 17: 57-96.\n[22]\tSchowalter D, Ghosh I, Kim S E, Haidari A. Unit-tests based validation and verification of numerical procedure to predict vortex-induced motion (C). Proceedings of OMAE2006, 25th International Conference on Offshore Mechanics and Arctic Engineering, Hamburg, Germany, 2006: 184-187."]}